PENGARUH MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DAN SELF EFFICACY SISWA - Irmayanti Irmayanti (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to study the interaction of Intellectual Auditory and Repetition (AIR) learning on mathematical problem solving abilities and self-efficiency of students in Class X of SMA Negeri 1 NA IX-X Aek Batu City. The population of this study was all students of class X SMA Negeri 1 NA IX-X Aek Batu City in the 2018/2019 academic year while the sample was class X-IPA 2 which was studied by 40 students. Data collection techniques using essay tests (pretest and posttest) were used for problem solving and the questionnaire was used for self efficacy. Data were analyzed using normality test, homogeneity test, and t-test. From these results, obtained tcount> ttable: 18.78> 1.83 and the significant value is smaller than the significant level value that is 0.002 <0.05. Therefore it is the Auditory Intellectually Repetition (AIR) learning model for students' mathematical problem solving abilities. For self efficacy, 80% results were obtained, thus positive student self efficacy towards the Auditory Intellectually Repetition (AIR) learning model. Can solve the problem of mathematical compatibility and significant student self-efficacy towards the Auditory Intellectualual learning model and the Repetition model.